2022
DOI: 10.3389/fmed.2022.1040168
|View full text |Cite
|
Sign up to set email alerts
|

Pre-anesthetic use of butorphanol for the prevention of emergence agitation in thoracic surgery: A multicenter, randomized controlled trial

Abstract: BackgroundEmergence agitation (EA) is common in patients after general anesthesia (GA) and is associated with poor outcomes. Patients with thoracic surgery have a higher incidence of EA compared with other surgery. This study aimed to investigate the impact of pre-anesthetic butorphanol infusion on the incidence of EA in patients undergoing thoracic surgery with GA.Materials and methodsThis prospective randomized controlled trial (RCT) was conducted in 20 tertiary hospitals in China. A total of 668 patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“… 4 Gao et al found that the incidence of EA in patients using propofol during general anesthesia can be up to 34%, 5 which leads to an increase in postoperative adverse events such as incisional dehiscence, tracheal tube displacement, falling off the bed, and cardiovascular events. 6 In severe cases, EA can also lead to self-harm, or violence against medical staff. 7 Remimazolam is a new anesthetic sedative with an ultra-short half-life that is metabolized by non-specific plasma esterases and does not accumulate during general anesthesia, 8 , 9 moreover, it has very slight hemodynamic impact.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Gao et al found that the incidence of EA in patients using propofol during general anesthesia can be up to 34%, 5 which leads to an increase in postoperative adverse events such as incisional dehiscence, tracheal tube displacement, falling off the bed, and cardiovascular events. 6 In severe cases, EA can also lead to self-harm, or violence against medical staff. 7 Remimazolam is a new anesthetic sedative with an ultra-short half-life that is metabolized by non-specific plasma esterases and does not accumulate during general anesthesia, 8 , 9 moreover, it has very slight hemodynamic impact.…”
Section: Introductionmentioning
confidence: 99%